THE ONSET OF CHAOS IN PULSATING VARIABLE STARS - Turner, D. G.; Berdnikov, L. N.; Percy, J. R.; Abdel-Latif, M. Abdel-Sabour (Одеські астрономічні публікації, 2010)
Random changes in pulsation period occur in cool pulsating Mira variables, Type A, B, and C semiregular variables, RV Tauri variables, and in most classical Cepheids. The physical processes responsible for such fluctuations are uncertain, but presumably originate in temporal modifications of the envelope convection in such stars. Such fluctuations are seemingly random over a few pulsation cycles of the stars, but are dominated by the regularity of the primary pulsation over the long term. The magnitude of stochasticity in pulsating stars appears to be linked directly to their dimensions, although not in simple fashion. It is relatively larger in M supergiants, for example, than in short-period Cepheids, but is common enough that it can be detected in visual observations of the stars, as demonstrated by the example of Delta Cephei. Although chaos was discovered in pulsating stars 80 years ago, detection of its general presence in the group has only been possible in recent studies.